Nanofluidic systems for ion transport with tunable surface charges: fabrications, characterizations, and applications - Shi, Dachuang; Zhou, Le; Li, Zhigang (Frontiers in Lab on a Chip Technologies, 2024)
Nanofluidics deals with the statics and dynamics of simple and complex fluids in systems with at least one dimension below 100 nm. Under strong nanoconfinements, flows may show diverse phenomena, which find rich applications in a variety of areas. In the past decades, nanofluidics has attracted great interest. Particularly, surface charge-governed ion transport in nanofluidic systems shows new flow fashions that cannot be observed in bulk systems and have been applied in different fields in science and engineering. These applications have motivated many efforts in developing surface charge-governed nanofluidic systems, including device fabrications and characterizations. Recent advances in nanotechnology have led to significant progress in surface modifications, which offer new opportunities for surface charge-governed nanofluidics systems. In this review, we discuss recent development of nanofluidic systems with tunable surface charges. Specifically, relevant theories, experimental approaches, and performance comparisons regarding the state-ofthe-art fabrication techniques, characterization methods, and applications are presented. Finally, we provide a perspective about the possible future topics and applications for advancing nanofluidic systems with tunable surface charge properties.